Security for wireless ad hoc networks - Anjum, Farooq (Wiley-Interscience, 2007)
This book addresses the problems and brings solutions to the security issues of ad-hoc networks. Topics included are threat attacks and vulnerabilities, basic cryptography mechanisms, authentication, secure routing, firewalls, security policy management, and future developments. An Instructor Support FTP site is available from the Wiley editorial board.